Good enough care? Looking after sexually abused young people in residential settings - Autumn Roesch-Marsh (Scottish Journal of Residential Child Care)
Sexual abuse in childhood is a traumatic and damaging experience that can have a range of effects for young people as they grow and develop. These can include increased risk of mental health difficulties such as depression and anxiety, psychological symptoms such as low self-esteem and guilt, and problem behaviours such as substance misuse (Avery, Massat & Lundy, 2000; Cotgrove & Kolvin, 1994; Haggerty, Sherwood, Garmezy & Rutter, 1996; Mental Health Foundation, 1999; Richardson & Joughin, 2000). A range of research has assessed the impact of sexual abuse and interventions which have been used to help protect against or alleviate resulting symptoms (Finkelhor & Berliner, 1995; Monck et al., 1996; Stevenson, 1999). Central to many of these studies has been the finding that involving the non-abusing parents of sexually abused children in any treatment approach greatly improves outcomes (Deblinger & Heflin 1996; Finkelhor & Berliner, 1995; Karp, Butler & Bergstrom, 1998). While many sexually abused young people remain in the care of their families, a significant number will be placed in substitute care settings. In such settings, opportunities for treatment may be influenced by a greater range of factors and will likely involve a wider range of professionals with less input from family members (Farmer & Pollock, 1998).